Cytotoxic Drugs Departments as a precondition for high-quality product - Głuszek, Katarzyna (Medical Studies/Studia Medyczne, 2014)
Cancer control is a tremendous challenge not only for the ill patient and physicians, but also for the whole health care system. For the first time, during the European Conference of Oncology Pharmacists, the highest standards of pharmaceutical care were proposed for cancer patients. Undoubtedly, the lifestyle and prophylaxis which would enable the detection of cancer at an early stage exert an effect on the development of the disease. Cytostatics show toxic, mutagenic, oncogenic and immunosuppressive effects; therefore, their preparation should be handled by the Central Cytotoxic Drugs Department, because the majority of the drugs prepared belong to Register A. Drugs are manufactured in accordance with GMP principles. All-Polish Standards adopted by the Polish Pharmaceutical Association delineate the direction to be developed by every hospital with respect to its own procedures and instructions. The Master of Pharmacy is responsible for the preparation of cytotoxic drugs. At one bench should work an operator and an assistant. The recommended working time should not exceed 2 h without break, and 5 h daily. The person who collects cytotoxic drugs from the Central Department should use a legible sign and a stamp including the hour and date of collection. While manufacturing cytostatics for patients in daily doses it is recommended to use concentrates in the form of solutions rather than lyophilised powders, which results in the shortening of the stage of production of the drug and reduces the possibility of forming aerosols; in the case of closed infusion systems (containers for infusion liquids) which are used for the production of daily doses, the cabinet should be equipped in two tight docks for dispensing. Needleless connection of the LUER-LOCK type – a recommendation of the ISOPP – guarantees a tight connection with the drug transfer port even in the case of an increase in pressure during the manufacture of drugs. To a certain extent a pharmacy becomes the producer and distributor of oncologic drugs. This is related with high requirements concerning the production of drugs (high quality), safety of the engaged staff, as well as participation in a rational management of medicines. According to the FIP, a pharmacy is a public health care facility where work is performed by authorised persons: Masters of Pharmacy and pharmacy technicians. At present the task of a clinical pharmacist also includes the supervision of activities in the area of clinical pharmacy. This is a new task for pharmacists, who are obliged to constantly expand their knowledge and actively participate in the activities of the medical team.